Women's rights in Islam and the challenge of modernity - Mohd Zin, Najibah (s.n, 2012)
Women rights in Islam remain a controversial subject since decades partly contributed by misconceptions in translating the law into practical reality. In another dimension, many cultural practices as commonly practiced by Muslims, particularly in Muslim countries often reflect negative treatments towards women. Therefore, this chapter will focus on fundamental aspect of women rights based on the premise that Islamic law has a comprehensive set of legal frameworks regulating women in elevating and determining their status in the society. The study includes contextual analysis of these principles when examining their practicality in the modern context